Lauric acid attenuates hepatic lipid metabolism by modulating the AMPK-SREBP pathway in high-fat diet-induced obese mice - Wong, Chi Hau; Fong, Lai Yen; Tengku-Muhammad, Tengku Sifzizul; Choo, Quok Cheong; Chew, Choy Hoong (Taylor and Francis, 2026)
Insulin resistance, characterized by a diminished cellular response to insulin signaling, is a central hallmark of metabolic disorders such as obesity and type 2 diabetes mellitus. This impaired responsiveness disrupts glucose and lipid homeostasis, leading to the progression of metabolic dysfunction. This study investigated the effects of lauric acid on lipid metabolism in male C57BL/6J mice. The mice were fed a high-fat diet for eight consecutive weeks to induce obesity, while the control group was fed a normal chow diet. Three experimental groups were co-treated with HFD and lauric acid (12 and 24 mg/kg orally), or HFD and rosiglitazone (20 mg/kg orally) for another eight consecutive weeks. Lauric acid reduced triglyceride levels while increasing HDL levels. Moreover, lauric acid upregulated hepatic expression of Apoa2, Pparg1 and Srebf2, and downregulated Hmgcr genes compared to HFD alone. Lauric acid treatment showed non-significant trends toward increased AMPK phosphorylation and decreased the total SREBP 1 and 2 protein in the liver. Histological examination revealed that lauric acid-fed mice showed similar hepatic morphology compared to the HFD control. Finally, the data suggest that lauric acid is a potential nutraceutical intervention for lipid-lowering and insulin resistance in obese individuals.